What constitutes the fat signal detected by MRI in the spine of patients with ankylosing spondylitis? A prospective study based on biopsies obtained during planned spinal osteotomy to correct hyperkyphosis or spinal stenosis - Baraliakos, Xenofon; Boehm, Heinrich; Bahrami, Reza; Samir, Ahmed; Schett, Georg; Luber, Markus; Ramming, Andreas; Braun, Juergen (Annals of the Rheumatic Diseases, 2019)
Objective: Study the MRI signal of fatty lesions (FL) by immunohistological analysis of vertebral body biopsies of patients with ankylosing spondylitis (AS) compared with degenerative disc disease (DDD). Methods: Biopsies obtained during planned surgery from vertebral edges where MRI signals of FL was detected were stained with H&E. Immunofluorescence (IF) staining was performed to quantify osteoblasts and osteoclasts. Bone marrow (BM) composition, grade of cellularity and quantification of cells were analysed on six randomly chosen high-power fields (HPF; 0.125 mm2) at 200-fold magnification per patient by two experienced researchers in a blinded manner. Results: Biopsies of 21 patients with AS and 18 with DDD were analysed. Adipocytes were found in the BM of 19 patients with AS (90.5%) versus 5 with DDD (27.8%) (p<0.001), while inflammatory infiltrates were found in in the BM of 8 patients with AS (38.1%) versus 14 with DDD (77.8%) (p=0.035) and fibrosis in 6 patients with AS (28.6%) versus 4 with DDD (22.2%) (p=n.s.). The most frequently detected cells were adipocytes in AS (43.3%) versus DDD (16.1%, p=0.002) and inflammatory mononuclear cells in DDD (55%) versus AS (11.0%, p=0.001). Using IF staining, there was more osteoblastic than osteoclastic activity (6.9 vs 0.17 cells/HPF) in FL as compared with inflammatory BM (1.3 vs 7.4 cells/HPF), respectively. Conclusion: MRI FL correspond to presence of adipocytes, resulting to change of cellular homeostasis towards diminution of osteoclasts in the BM of patients with AS. The cross-talk between the different cell types and osteitis, fat and new bone formation needs further study.
CRIS-Team Scopus Importer:2019-06-04
Keywords: axial spondyloarthritis; biopsy; fatty lesions; magnetic resonance imaging